(untitled) (Medico Legal Update, 2021)
Background: Adolescence is the period of rapid growth with physical & physiological development and profound biological, emotional, social, and cognitive changes in human beings. Nutritional anemia is the common & worldwide public health problem among adolescent girls and overall prevalence of nutritional anemia varies from 40-90%. It may produce adverse effects like increased risk of morbidity and mortality and affects adolescent’s future health. Objective: This study aimed to assess the awareness on nutritional anemia and its prevention among adolescent girls. Method: A non experimental descriptive design was adopted to assess awareness on nutritional anemia and its prevention among adolescent girls at Keezhakasakudi, Karaikal. A total of 60 adolescent girls between 10-15 years of age were selected by convenience sampling technique. Data was collected by using self structured interview schedule. Both descriptive and inferential statistics were used to analysis the gathered data. Results: The study results reported that the majority 63% (38) of adolescent girls had inadequate awareness, 27% (16) had moderately adequate awareness and only 10% (6) had adequate awareness on nutritional anemia and its prevention. The overall mean was 9.6 with standard deviation±2.49. The results of the present study also revealed that there was statistically significant association between level of awareness on nutritional anemia with age of the adolescent girls. Conclusion: Nutritional anemia as the major non communicable disease and contributing negative impact on health, it necessitates the need to organize counseling programs to adolescent girls in schools and colleges with much emphasis on impact of nutritional anemia on future health.